P01.046 Complete radiological response under treatment with Tumor Treating Fields following subtotal resection in a series of three Glioblastoma patients. (19th September 2018) - Kessler, A; Linsenmann, T; Westermaier, T; Wolber, W; Hagemann, C; Ernestus, R; Löhr, M
Abstract: Background: After subtotal resection (STR), residual contrast-enhancing glioblastoma multiforme (GBM) rarely undergo complete regression following radiochemotherapy and adjuvant chemotherapy. Moreover, in comparison to gross total resection (GTR) overall survival (OS) and progression-free survival (PFS) is significantly decreased in GBM patients with STR. GBM therapy following resection consists of radio- and chemotherapy with Temozolomide (TMZ). In addition Tumor Treating Fields (TTFields), low intensity (1–3 V/cm), intermediate frequency (100–300 kHz) alternating electric fields, are applied during adjuvant chemotherapy. The addition of TTFields led to a significant increase in PFS, OS and long-term survival in the EF-14 phase III trial. Here, we report three patients with subtotally resected GBMs localized in eloquent areas. These patients received TTFields (200 kHz) in addition to TMZ after surgery and radiochemotherapy. All patients showed complete radiological response (CR) under TTFields therapy. Case presentation: A 54-year-old woman with primary IDH1/2-wildtype and O6-methylguanine-DNA methyltransferase promoter methylated GBM (IDH1/2 WT, MGMT+) received combined radiochemotherapy after STR. TTFields therapy was initiated in parallel to 6 cycles of adjuvant TMZ. CR was observed after 5 months of TTFields treatment and remained stable for 7 months before new tumor growth was detected. A 46-year-old woman with a primary GBM, IDH1/2 WT, MGMT+, sustained nuclear ATRX expression (ATRX+) received combined radiochemotherapy followed by 6 cycles of TMZ after STR. TTFields were initiated simultaneously to the first cycle of adjuvant TMZ and continued for 6 months. CR was seen after 4 months of TTFields treatment, for 16 month up to date no recurrent tumor growth occurred. A 44-year-old man developed a secondary GBM (IDH1 WT, MGMT+) while receiving radiochemotherapy according to the Stupp-protocol due to an anaplastic astrocytoma WHO°III (cycle 4 of TMZ). Concomitant to additional 6 cycles of TMZ, TTFields therapy was initiated 4 months after STR and was continued for 37 months. After 35 months of ongoing TTFields treatment as monotherapy CR is still stable. Conclusion: We report on three GBM patients with newly diagnosed and recurrent GBM who underwent STR, radiochemotherapy and were subsequently treated with temozolomide and TTFields at our institution. The reported patients showed complete radiological responses under TTFields treatment.